Adobe photoshop element 9 : digital classroom (Wiley Publishing, 2010)
Photoshop Elements 9 Digital Classroom is like having your own personal instructor guiding you through each lesson, while you work at your own pace. This book includes 13 self-paced lessons that let you discover essential skills and explore new features and capabilities of Adobe Photoshop Elements. Each lesson includes step-by-step instructions, lesson files, along with video tutorials that complement the topics covered in each lesson. These accompanying files are provided on the included DVD and are developed by the same team of Adobe experts who have created many of the official training titles for Adobe Systems. Each tutorial is approximately five minutes long and demonstrates and explains the concepts and features covered in the lesson. This training package demonstrates how to edit and apply effects for stellar digital images, painting and retouching, and exploring the different filters and techniques that tap into ones creative side to produce great images